Folkloric uses of Jatropha gossypifolia in emesis and gut motility disorders: Pharmacological validation (Bangladesh Journal of Pharmacology, 2015)
Jatropha gossypifolia is used in folkloric system to manage emesis and gastrointestinal motility disorders such as constipation and diarrhea. The present study was undertaken to provide pharmacological evidences for these folkloric uses by in vivo and in vitro experimental setting. Ethanolic extract of J. gossypifolia showed the significant antiemetic potential (p